MAPPING POROSITY VARIATION IN A WELDED PYROCLASTIC DEPOSIT WITH SIGNAL AND VELOCITY PATTERNS FROM GROUND-PENETRATING RADAR SURVEYS - Rust A.C.; Russell J.K. (My University, 2001)
Ground-penetrating radar (GPR) is used to both image and quantify porosity variations in a variably welded pyroclastic flow deposit. Characteristic radar signals for nonwelded (constant, high porosity) and welded (porosity lower and variable) zones are identified by comparison of radar signals to exposed stratigraphy. A moderate rate of change in porosity with depth generates abundant, unresolvable reflections. A relatively constant porosity results in a flat, zero-amplitude response. Lastly, a discrete jump or extremely high rate of change in porosity (abrupt at scale of radar wavelength) can produce a strong, distinct reflection. Common-midpoint (CMP) survey data are analyzed to determine relative radar velocity patterns in the pyroclastic flow. Changes in radar velocity are linked to changes in relative porosities that are attributed to differential welding. Our analysis shows that welding causes substantial reductions in radar velocity. Moisture in subsurface stratigraphy also strongly affects velocity. Therefore, we advocate the interpretation of radar data in terms of relative changes in porosity. Our results also suggest that, in areas of rapid facies changes, multiple CMP surveys are required for accurate conversions of travel time to depth.
Keywords: GROUND-PENETRATING RADAR; COMMON MIDPOINT SURVEY; VELOCITY; POROSITY; PYROCLASTIC; WELDING; WATER